2019
DOI: 10.1080/21691401.2019.1606010
|View full text |Cite|
|
Sign up to set email alerts
|

6-Gingerols (6G) reduces hypoxia-induced PC-12 cells apoptosis and autophagy through regulation of miR-103/BNIP3

Abstract: 2019) 6-Gingerols (6G) reduces hypoxia-induced PC-12 cells apoptosis and autophagy through regulation of miR-103/BNIP3, Artificial ABSTRACT Finding novel therapeutic agent for the treatment of cerebral ischemia is urgently required. These experiments explored the potential roles of 6-Gingerols (6G) in hypoxia-stimulated rat PC-12 cells. Cell viability, apoptosis and its related proteins were studied by the approaches of MTT assay, flow cytometry assay and Western blot analysis, respectively. In addition, wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…To explore the mechanism of HIF-1α on mitophagy activation, we investigated the expression HiF-1α/BNIP3 classical signaling pathway in the chondrocytes treated with DMOG under hypoxia. The BNIP3 expression is necessary for hypoxia-induced autophagy activation and BNIP3 knockdown aggravated cell death during hypoxia 54,55 . In agreement with these previous studies, our study showed that the BNIP3 expression increased in a dose-dependent manner following the DMOG-induced HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the mechanism of HIF-1α on mitophagy activation, we investigated the expression HiF-1α/BNIP3 classical signaling pathway in the chondrocytes treated with DMOG under hypoxia. The BNIP3 expression is necessary for hypoxia-induced autophagy activation and BNIP3 knockdown aggravated cell death during hypoxia 54,55 . In agreement with these previous studies, our study showed that the BNIP3 expression increased in a dose-dependent manner following the DMOG-induced HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Similarly, 6-gingerol protected against hypoxia-stimulated PC-12 cells by inhibiting p38 MAPK and JNK pathways. [41] A previous study has demonstrated that activation of the p38 MAPK and JNK pathways by various stimuli including hypoxia, are associated with apoptotic cell death. [42] Yasodai and colleagues [43] elucidated that, gingerol protected against cell death induced by MPP + via antioxidant effects by decreasing the level of ROS and improved the function of respiratory complex I in human caucasian neuroblastoma cells as a cellular model of PD.…”
Section: Discussionmentioning
confidence: 99%
“…6-Gingerols, which is a phenolic ingredient first purified from ginger, has been reported to exert anti-inflammatory [61] and anti-oxidative effects [62]. Remarkably, in the era of neuroprotection, 6-Gingerol has been demonstrated to protect against hypoxia-induced apoptosis of PC-12 cells by upregulating the neuroprotective microRNA (miR) miR-103 [63]. Furthermore, recent evidence has shown that 6-Gingerol can attenuate lipopolysaccharide-induced neuro-inflammation in vitro and in vivo by suppressing astrocyte overactivation [61].…”
Section: Discussionmentioning
confidence: 99%